The Role of Stakeholders in The Development of Educational Technology-Based Agricultural Tourism - Jimmy Ruben Sihombing; Kurniawan Saefullah; Edwin Rizal; Evi Novianti; Annisa Lazuardina (JTP - Jurnal Teknologi Pendidikan, 2025)
Ciherang Village, located in Nagreg District, Bandung Regency, West Java, has strong potential for the development of sustainable agricultural educational tourism, supported by its natural, cultural, and socio-economic resources. However, this potential has not been optimally developed due to limited coordination among stakeholders and uneven readiness in adopting educational technology. This study aims to analyze the roles and positions of stakeholders in developing agricultural educational tourism in Ciherang Village by integrating an educational technology perspective through the pentahelix approach. This research employs a qualitative descriptive method. Data were collected through observations, in-depth interviews, and documentation involving key stakeholders, including local government officials, tourism awareness groups (Pokdarwis), community members, business actors, academics, and media. The data were analyzed narratively and organized into matrices to examine stakeholder involvement, roles, responsibilities, and readiness in utilizing educational technology, including infrastructure and digital literacy. The findings indicate that effective collaboration among stakeholders is essential for strengthening agricultural educational tourism development. The use of educational technologies, such as digital applications, QR codes, social media, and AR/VR-based content, enhances visitors’ learning experiences and improves the competitiveness of the tourism village. Nevertheless, challenges remain, particularly related to infrastructure limitations and disparities in technological capacity. This study provides insights for developing innovative and sustainable agricultural educational tourism through multi-stakeholder collaboration.